Gender differences in banana productivity in Tanzania - Hildo Ladislaus Mrema; Razack Bakari Lokina; Onesmo Selejio (Interdisciplinary Journal of Rural and Community Studies)
Banana is one of the key crops produced by farmers in Tanzania. The productivity of bananas among smallholder farmers is very low. One of the core reasons for this lower agricultural productivity in Tanzania is gender inequality in production. This study aimed to establish gender productivity differences in banana production in Tanzania. The study used panel data and a correlated random effects (CRE) model to determine these differences. It finds a 19% difference in banana productivity in favour of male managers, highlighting their (plot managers') characteristics, input use, and banana plot characteristics. The area of banana cultivation by zones, namely Lake, Northern, Southern Highlands, and Eastern zones, was found to increase banana productivity. The use of organic fertiliser and receiving government extension services have a positive influence on banana productivity. On the other hand, being a female manager, an increase in banana plot area, and an increase in the usage of pesticides have a detrimental effect on banana productivity. The findings of this study suggest the need for proper banana plot management, farmer training on skills such as the timing and amount of inputs that can be applied to banana plots sustainably, and the availability of extension services to all plot managers, regardless of their gender. Additionally, the study advocates for the sustainable use of pesticides by adopting good agricultural practices like Integrated Pest Management (IPM) and using appropriate planting materials that are disease-resistant.